Photochemical CO2 Reduction Using Rhenium(I) Tricarbonyl Complexes with Bipyridyl‐Type Ligands with and without Second Coordination Sphere Effects. Issue 6 (1st March 2021) - Rotundo, Laura; Grills, David C.; Gobetto, Roberto; Priola, Emanuele; Nervi, Carlo; Polyansky, Dmitry E.; Fujita, Etsuko
Abstract: The effect of phenyl, phenol, aniline, amino, and CF3 substituents of the 2, 2′‐bipyridine ligand in fac ‐ReCl(L)(CO)3 (L=2, 2′‐bipyridine derivative) catalysts on photochemical CO2 reduction in dimethylacetamide is examined, in order to understand the structure‐function relationships and to compare the catalytic activities with the previously published electrochemical results. All complexes including ReCl(bpy)(CO)3 have similar excited‐state lifetimes and emission spectra, but complex 1 with the Ph‐NH2 moiety exhibits a significantly larger molar absorption coefficient for its metal‐to‐ligand charge transfer (MLCT) band. All complexes we tested produce CO with only a negligible amount of H2 and formate in self‐sensitized systems in the presence of triethanolamine (TEOA) and in some cases, BIH (1, 3‐dimethyl‐2‐phenyl‐2, 3‐dihydro‐1H‐benzo[ d ]‐imidazole). The presence of the Ph‐NH2 moiety (complex 1 ) has a beneficial effect on both electrochemical and photochemical activity, allowing a turnover number (TON) of 32 and 120 for photochemical CO production (without and with BIH, respectively). In the case of the Ph‐OH group in the second coordination sphere (complexes 4 and 6 ), these complexes are active for photochemical CO2 reduction, despite the formation of a stable 6‐coordinate Re‐OPh intermediate via reductive deprotonation as previously observed under electrochemical conditions. Overall, BIH accelerates the rate of formation of the one‐electron reduced species (OERS) of the Re catalysts and allows higher turnover frequency (TOF) and TON for CO formation. The X‐ray structures of complexes 1 and 4 were determined to have distorted octahedral Re centres, and show π‐π stacking interactions with neighboring molecules as well as intramolecular hydrogen bonds to the internal chloride ligands. The unusually high absorptivity of the MLCT absorption of complex 1 has been explained by TD‐DFT calculations. Abstract : Rhenium in action : The effect of phenyl, phenol, aniline, amino, and CF3 substituents of the 2, 2′‐bipyridine ligand in fac ‐ReCl(L)(CO)3 (L=2, 2′‐bipyridine derivative) complexes has been examined in order to understand the structure‐function relationships and to compare the catalytic activities for photochemical CO2 reduction in dimethylacetamide with and without BIH (1, 3‐dimethyl‐2‐phenyl‐2, 3‐dihydro‐1H‐benzo[ d ]‐imidazole).